2014
DOI: 10.1093/neuonc/nou045
|View full text |Cite
|
Sign up to set email alerts
|

Significance of interleukin-13 receptor alpha 2-targeted glioblastoma therapy

Abstract: Glioblastoma multiforme (GBM) remains one of the most lethal primary brain tumors despite surgical and therapeutic advancements. Targeted therapies of neoplastic diseases, including GBM, have received a great deal of interest in recent years. A highly studied target of GBM is interleukin-13 receptor α chain variant 2 (IL13Rα2). Targeted therapies against IL13Rα2 in GBM include fusion chimera proteins of IL-13 and bacterial toxins, nanoparticles, and oncolytic viruses. In addition, immunotherapies have been dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 76 publications
(101 reference statements)
1
111
0
Order By: Relevance
“…Two Phase 1 clinical trials were performed with intracranial administration of first-generation IL-13 zetakine T cell clones in patients with high-grade gliomas [152]. In the pilot trial, 3 participants with recurrent/refractory GBM were treated with autologous first generation IL-13 zetakine T-cell clones in escalating cell dose infusion cycles (NCT00730613) [153].…”
Section: Chimeric Antigen Receptor-modified T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Phase 1 clinical trials were performed with intracranial administration of first-generation IL-13 zetakine T cell clones in patients with high-grade gliomas [152]. In the pilot trial, 3 participants with recurrent/refractory GBM were treated with autologous first generation IL-13 zetakine T-cell clones in escalating cell dose infusion cycles (NCT00730613) [153].…”
Section: Chimeric Antigen Receptor-modified T Cellsmentioning
confidence: 99%
“…All 6 patients were treated in conjunction with IL-2 with repetitive doses of CAR T cells. In both clinical trials, the feasibility of this approach was demonstrated [152]. Because all types of CAR-T cells expressing IL-13 or its mutants will bind to IL-13Ra1 in tumor and non-tumor cells, the investigators should be careful in monitoring on-target and off-target toxicity closely.…”
Section: Chimeric Antigen Receptor-modified T Cellsmentioning
confidence: 99%
“…The first-generation CAR-modified T cells targeted to IL13Rα2 produced impressive results in preclinical studies, curing mice with intracranial glioma without any recurrence. In phase I trials, they were found to be safe and capable of trafficking to distant sites of infiltrative disease [35]. Second-generation IL13Rα2-CAR T cell clones linked to CD28 costimulatory molecule and CD3 are awaiting trials and may offer superior efficacy.…”
Section: Immunotherapiesmentioning
confidence: 99%
“…A number of TAAs have been identified in glioblastoma, including EphA2, Her2, IL13Ra2, gp100, Mage-1, survivin, hTERT, AIM2, and EGFR (Koka et al, 2003;Tchirkov et al, 2003;Liu et al, 2004a, b;Heimberger et al, 2005;Wykosky and Debinski, 2008;Shirai et al, 2009;Thaci et al, 2014). The discovery of glioblastomaspecific antigens has led to the development of vaccines targeted against them.…”
Section: Vaccination Therapymentioning
confidence: 99%